Application of Quercetin in the Treatment of Gastrointestinal Cancers - Mirazimi, Seyed Mohammad Ali; Dashti, Fatemeh; Tobeiha, Mohammad; Shahini, Ali; Jafari, Raha; Khoddami, Mehrad; Sheida, Amir Hossein; EsnaAshari, Parastoo; Aflatoonian, Amir Hossein; Elikaii, Fateme; Zakeri, Melika Sadat; Hamblin, Michael R; et al. (Frontiers in Pharmacology, 2022)
Many cellular signaling pathways contribute to the regulation of cell proliferation, division, motility, and apoptosis. Deregulation of these pathways contributes to tumor cell initiation and tumor progression. Lately, significant attention has focused on the use of natural products as a promising strategy in cancer treatment. Quercetin is a natural flavonol compound widely present in commonly consumed foods. Quercetin has shown significant inhibitory effects on tumor progression via various mechanisms of action. These include, stimulating cell cycle arrest or/and apoptosis, as well as its anti-oxidant properties. Herein, we summarize the therapeutic effects of quercetin in gastrointestinal cancers (pancreatic, gastric, colorectal, esophageal, hepatocellular, oral).